Determinant factors of turnover versus permanence of portuguese repatriates: an exploratory study - Martins, Dora (2015)
The study seeks to identify the determinant factors of the repatriate’s decision to remain or leave the company after repatriation, in a convenience sample of 40 Portuguese returnees working in companies based in Portugal. The main results were as follows: (1) there are seven factor categories: (a) salaries and benefits; (b) possibility of promotion, development, professional development; (c) organizational support (during and after the international mission) recognition of work; (d) economic and social atmosphere of the company, (e) good relationship with leadership; (f) convenience and/or personal / family well-being and; (g) external alternatives; (2) the main factors leading to permanence are (a) possibility of promotion, development and professional development and; (b) the existence of personal and family well-being / convenience; (3) the main factors leading to abandonment are (a) lack of organizational support and recognition of work performed; (b) lack of possibility of promotion, development and professional development and; (c) lack of personal / family well-being / convenience. Globally, the study suggests that the factors leading to permanence are very similar to those that lead to abandonment, although in reverse.